Produção de biohidrogênio com água residuária de fecularia de mandioca em reator contínuo de tubos múltiplos - Souza, Willyan Goergen de (2020)
Many studies on hydrogen production by dark fermentation encounter difficulties in maintaining stability and continuity over time. The lack of a proper biomass control in the system is pointed out as one of the main causes of this instability and discontinuity. The balance of food/microorganism ratio can be better evidenced by the SOLR (specific organic loading rate). The configuration of the continuous multiple tube reactor (CMTR) is based on the premise of controlling this parameter through the facilitated and successive disposal of older biomass. The renewal of the microorganisms in the system is favorable for hydrogen production. However, in some initial tests, the retention of biomass in the walls of the tubes was not sufficient to guarantee the continuity of production. In a recent study, internal grooves were applied to the tubes to overcome this problem, considerably improving the results. However, more tests with real effluents are necessary to verify the behavior of biohydrogen production in this reactor model. This work compared two inoculum sources (thermally treated anaerobic sludge and self-fermented synthetic wastewater) fed with cassava processing wastewater (CPWW) in the CMTR. In addition, two constructive configurations (12 and 16 tubes) were tested, totaling 3 assays: R1 (12 tubes - self-fermented); R2 (12 tubes - anaerobic sludge); and R3 (16 tubes - anaerobic sludge). The HRT was set to 4 h with an initial pH adjusted to 6.0 and temperature kept constant at 25ºC. The assay R1 stopped the biogas production with 14 days of CPWW feeding. Assay R2 presented an average VHPR of 0.14 and a maximum of 0.56 LH2.L-1 REACTOR.d-1 and an average HY of 0.12 and a maximum of 0.55 molH2.mol-1 CARB. Despite remaining in operation for 121 days, it showed high instability throughout the period, maintaining better production rates for up to 70 days. Assay R3 remained in operation for 62 days, period that resulted in an average PVH of 0.07 and a maximum of 0.18 LH2.L-1 REACTOR.d-1 and the average HY was 0.03 with a maximum value of 0.11 molH2.mol-1 CARB. This reactor took up to 20 days to start producing biogas. The efficiency of carbohydrate conversion of the three reactors showed averages close to 80%. SOLR analyzes indicated excessive biomass accumulation, which may have impaired the biohydrogen production. Samples of CPWW with a high organic load negatively influenced hydrogen yield. The thermally treated anaerobic sludge inoculum showed to be more efficient to be submitted to real wastewaters. The 16-tube configuration did not have an efficient distribution of the feed flow. Despite the operational difficulties, it was possible to achieve progress in the continued production of biohydrogen from real wastewater using the CMTR system.